Association between processes of diabetes care and health care utilization in patients with diabetes: Evidence from a nationally representative US sample. Issue 1 (13th September 2020) - Delevry, Dimittri; Ho, Anh; Le, Quang A.
Abstract: Background: This study examined the association between quality of processes of diabetes care in terms of adherence to American Diabetes Association (ADA)‐recommended guidelines and health care utilization in patients with diabetes. Methods: Adults with diabetes were identified from the pool of five panels of the Medical Expenditure Panel Survey, a nationally representative US sample, between 2012 and 2017. The Diabetes Care Survey was used to determine adherence to the ADA‐recommended guidelines for processes of diabetes care if all of the following were performed annually: glycosylated hemoglobin check, foot examination, dilated eye examination, lipid panel, influenza immunization, blood pressure check, and dental examination. Health care utilization in terms of inpatient hospitalization, and emergency department (ED) and outpatient visits were estimated using two‐part hurdle models. Results: An estimated 26.3 million adults with diabetes were derived from the pooled 5‐panel data, of which 7.8% met the ADA‐recommended guidelines for processes of diabetes care, and adherence rates of individual recommendations were generally below 50%. Overall, adults who adhered to the ADA‐recommendations were older, non‐Hispanic white, and married nonsmokers with private insurance and higher income. Mean inpatient hospital stays, ED, and outpatient visits between ADA‐adherent vs nonadherent patients were 0.98 vs 1.62 ( P < .001), 0.36 vs 0.39 ( P = .074), and 17.9 vs 12.8 ( P < .001), respectively. Conclusions: Socioeconomic disadvantage and minority status were linked with nonadherence to the ADA‐recommended processes of diabetes care. Adherence to the ADA recommendation was associated with significant reduction in inpatient hospitalization and a trend toward less ED visits. Our findings may apply to the United States and are likely to be different in other parts of the world. Abstract : Highlights Approximately 7.8% of patients with diabetes adhered to the American Diabetes Association (ADA) annual guidelines for components of health care services with adherence rates of individual recommendations generally being below 50%. Socioeconomic disadvantage and minority status were associated with nonadherence to the ADA‐recommended guidelines. Additionally, this study provides evidence that adherence to the ADA‐recommended processes of diabetes care was associated with significant reduction in inpatient hospitalization and a trend toward less emergency department visits. 摘要: 背景: 这项研究调查了糖尿病患者遵循美国糖尿病协会(ADA)推荐指南的糖尿病护理过程质量与卫生保健使用情况之间的关系。 方法: 2012~2017年, 从具有全国代表性的美国医疗支出固定样本调查的五个合并样本中确定成年糖尿病患者。糖尿病护理调查被用来确定是否遵守ADA推荐的糖尿病护理流程指南, 前提是每年进行以下所有检查:糖化血红蛋白检查、足部检查、眼底检查、脂类检查、流感免疫接种、血压检查和牙科检查。在住院、急诊科和门诊就诊方面的卫生保健利用情况使用双栏模型进行估计。 结果: 根据汇集的5个样本数据大约2 630万成人糖尿病患者资料, 7.8%符合ADA推荐的糖尿病护理流程指南, 每条推荐建议的遵从率低于50%。总体而言, 遵守ADA建议的成年人是老年人、非西班牙裔白人, 以及有私人保险和较高收入的已婚非吸烟者。ADA依从者与非依从者之间的平均住院天数、急诊和门诊次数分别为0.98 vs 1.62( P <0.001)、0.36 vs 0.39( P =0.074)和17.9 vs 12.8( P <0.001)。 结论: 社会经济劣势和较低地位与不遵守ADA推荐的糖尿病治疗流程有关。遵守ADA的建议与住院人次的显著减少和急诊室就诊次数减少的趋势有关。我们的发现可能适用于美国, 而在世界其他地区可能会有所不同。